World literature, a decentred sphere. (2019)
Franco Moretti and Pascale Casanova’s accounts of world literature are coded in metaphors. The former employs a core-periphery system to examine the unequal relationships between national literatures; the latter sees world literature as a ‘world literature of letters’, wherein the exchanges between literary traditions take place following economic patterns. This essay discusses to what extent these metaphors are inadequate to analyse the current trends of world literature as they portray the so-called central literatures as unidirectional forces that inform the canon, thereby shaping the literary production. This perspective privileges an economical jargon which constitutes an ideological bias resulting in the homogenisation of the literary value. This article takes a different approach by offering an alternative metaphor to explain world literature and its dynamics. This metaphor is a decentred sphere without a circumference. In order to illustrate this point, William Ospina’s El año del verano que nunca llegó (2015) is analysed, focusing on its worldly elements.